The strengthening of the national transparency authority`s regulations as a strategy to fight corruption in the public administration - Cárdenas Arce, Heidi Soraya (2022)
This article tries to analyze the need to strengthen the National Authority for Transparency and Access to Public Information´ regulations in order to convert it into a specialized public body with a high degree of independence that grants it greater operational capacity in order to face the problems related to non-compliance with the rules of transparency and access to public information and follow with the recommendations of international organizations such as the Organization of American States, the Organization for Economic Cooperation and Development and the Access of information Model Law; all of this as an strategy to fight corruption in the Public Administration because the attention to requests for access to public information allow citizen participation in the public administration acts.